Evaluating the compatibility between Indonesian language teachers’ competence, their needs, and in-service training’s effectiveness - Henry Wijaya; Veronica Christamia Juniarmi; Christa A. Y. Tehusalawany (LITERA, 2022)
BIPA’s growth is observable from APPBIPA’s expansion, teachers dispatch to various countries, and the soaring number of host institutions. The growth, which leads to the escalating number of teachers, needs to be met with elevated competence, whereas the mushrooming in-service training requires critical evaluation to ensure impactful results. This research examines the compatibility between teacher’s standard of competence, what they need to attain it, and the effectiveness of training programs in bridging those two. While generally satisfied with the training topics, methods, content, and trainer, the participants still deemed those aspects to be not fully compatible with their needs, nor to be fully effective in achieving the competence standard. Considering its importance, in-service BIPA teacher training not just exist but lack of/without meaningful impacts. Finally, the writers expect the results of this study to inform more effective BIPA training programs in the future.Keywords: competence, teachers training, in-service, evaluation, effectiveness